Optimizing the Utilization of Local Food Resources for Stunting Prevention through "MPASI" Training in Sumber Village, Simo District, Boyolali Regency.: Optimalisasi Pemanfaatan Sumber Daya Pangan Lokal untuk Pencegahan Stunting melalui Pelatihan MPASI di Desa Sumber, Kecamatan Simo, Kabupaten Boyolali - Fitri Astutiningsih; Rini Wulandari (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Sumber village, located in Simo district, Boyolali regency, faces a serious stunting problem. Stunting occurs due to prolonged nutritional deficiencies during critical growth periods in children, which are closely linked to cognitive development and long-term health risks. According to the Boyolali Health Department (2024), there has been an 8.9% increase in stunting cases, amounting to 4.913 cases in the Boyolali regency, with Simo district contributing 111 cases. To address this issue, the FATIPA UNISRI Community Service Team implemented a program to enhance knowledge and skills in preparing Complementary Foods for Breast Milk (MPASI) using locally available ingredients. This training was held in two sessions. "The first initiative focuses on stunting prevention outreach, while the second involves hands-on training in preparing MPASI." The results showed a significant increase in participants' knowledge and skills regarding stunting prevention and nutritious MPASI preparation, which is expected to reduce the prevalence of stunting in the village.